Carpocrinus (Echinodermata: Crinoidea) from the Late Silurian of Somerset Island, Northwest Territories, Canada - Frest, T. J.; Strimple, H. L. (Canadian Journal of Earth Sciences, 1977)
Carpocrinus arcticus n. sp. is the first Silurian crinoid to be reported from Arctic Canada (Read Bay Formation, Somerset Island). The species is distinguished from other North American Carpocrinus by its nonlobate calyx, plates with impressed sutures, and granular plate ornamentation. It is a member of a largely European lineage not previously reported from North America. The typical North American lineage was considered a separate genus (Stiptocrinus) by Kirk: it is here considered synonymous with Carpocrinus. Review of the stratigraphic distribution of Carpocrinus occurrences indicates that the lineage including C. arcticus is characteristic of Late Wenlock-Ludlow rocks.